Genetic factors enhancing seed longevity in tropical japonica rice - Raquid, Rency; Kohli, Ajay; Reinke, Russell; Dionisio-Sese, Maribel; Kwak, Jieun; Chebotarov, Dmytro; Mo, Youngjun; Lee, Jae-Sung (Elsevier, 2021)
Seed longevity is a key trait to secure seed viability and vigor of farmer’s seed lots under the increased temperatures and humidity associated with climate change. While previous studies have found quantitative trait loci (QTL) for improved longevity in temperate japonica rice varieties, there are no available QTL identified that can potentially enhance seed longevity in tropical japonica rice, which are grown in ASEAN countries and highly vulnerable to the impact of climate change. Here, we present QTL and candidate genes identified in an F3 bi-parental QTL mapping population developed from a tropical japonica × indica cross, using 1 k single nucleotide polymorphism (SNP) markers. To accelerate seed ageing through a seed storage experiment, seed moisture content (MC) was elevated by equilibrating seeds at 60 % relative humidity (RH) and 20 °C, after which seeds were stored at 10.9 % seed MC and 45 °C for 56 days. Within a QTL identified on chromosome 2 (2.9 Mb size), there were 45 annotated genes potentially relevant to seed longevity mechanisms such as oxidative stress reduction and repair of damaged DNA. Within the QTL, the preponderance of genes expressed largely in reproductive tissues, seeds or embryo make this a dependable QTL. Based on coexpression and network analysis, we highlight eight genes as potentially important candidate genes, consistent with previous studies suggesting their role in seed germination and longevity.